Contents Vol. 38 No. 2 July-December 2023 - Philip J Otolaryngol Head Neck Surg (Philippine Journal of Otolaryngology Head and Neck Surgery, 2023)
EDITORIAL 4 On the Brink: The Climate and Nature Crisis and Risks of Nuclear War